Part-timers’ perspectives on training: a study of Thai students in Nottingham, United Kingdom - Angpaibul, Sirin (2016)
Part-time workers typically receive fewer fringe benefits and training compared to full-timers. Only few available published papers mention the employees’ views on training. By using the one-to-one semi-structured interview with the Thai part-timers in Nottingham, this study focuses on their perspectives of the training method and its sufficiency, usefulness, and appropriateness. Based on the human capital theory, the findings reveal that most of the employers use the on-the-job training method to train their part-time staff as they are concerned about the return on their investment. However, the training received from the employers is not enough. Due to the time constraints, part-timers illustrate that trainings only help them to get the job’s overview. Another obstacle for the foreign students working abroad is the language barrier. In contrast to the previous studies, the results show that the part-timers are motivated to participate in training programme as they have no background and want to do their best in the position. They also recommend the employers to devote more time to trainings, revision sessions and communicating the main key points of each task before the job starts. By taking those comments into consideration, the employers can make the best use of their workers.